Strategies of Islamic Schools in Preparing for Accreditation A (Case Study of Muhammadiyah 05 Elementary School in Semarang) - Alfiyaturohmaniyyah, Shicha; Warsiyah, Warsiyah; Muflihin, Ahmad (Universitas Islam Sultan Agung, 2023)
Regulation of the Minister of National Education No. 63/2009 highlights the policy of improving the quality of education through the accreditation process in schools. BAN-S/M accreditation data in 2018 indicated that out of 51,979 Schools/Madrasahs accredited A as much as 20.51% and accredited B as much as 55.31%, showing the dominance of B accreditation and indicating that the achievement of education quality in Indonesia is still not optimal. This study aims to describe the strategies of Islamic Schools, particularly SD Muhammadiyah 05, in preparing for A Accreditation. Qualitative research using a case study approach involved observation, interviews, and documentation. Data triangulation with data analysis techniques, such as data reduction, data presentation, and conclusion drawing, were used to ensure data validity. The research object involved the environment of SD Muhammadiyah 05 with respondents from various parties, including the principal, staff, teachers, and students. The results showed that the strategies implemented by the school have progressed, as evidenced by the achievement of a score of 91 or A Accreditation. The strategies such as conducting socialization to stakeholders, analyzing the requirements of A accreditation, forming an accreditation team, school self-evaluation (EDS), training and development of human resources, improving facilities and infrastructure and commitment to improvement are continuously pursued to ensure compliance with accreditation standards and improve the overall quality of education.